Qualidade de vida, saúde bucal e autopercepção de saúde bucal em uma amostra de idosos - Damasceno, Anderson Medeiros (2010)
The aims of this study were to know the quality of life (QOL), to report the oral health by means of caries experience, to assess the self-perception of oral health, and to relate these three factors in a sample of elderly. For the data collection the tools WHOQOL-BREF, DMFT index, and GOHAI were used. It is a paired 1:3, descriptive study for sex and age, and its sample was consisted of 69 functionally independent elderly,17 being institutionalized and 52 non-institutionalized. The findings allowed to note that 80% of the individuals are female and the predominant age range is between 60 to 69 years. The QOL was assessed as “good” by 53.6% of the sample and the statistically significant differences are in the physical, psychological, and social relationships fields (WHOQOL-BREF). The DMFT index ranged from 17 to 28, and the edentulism rate found was 71% for the institutionalized elderly and 40% for those non-institutionalized. It was noted higher percentage of use of dental prosthesis in the upper arch. Concerning the self-perceived oral health it were found that the studied elderly evaluate their oral health as excellent or fair, although the mean GOHAI is 27.13, scoring as negative the oral health. It was concluded that there was no relation between QOL and oral health status and self-perception of oral health. The QOL was considered good in the studied sample, the edentulism was in both groups determining a high DMFT index, and the self-perception of oral health was negative for both groups of elderly. It is suggested implementing public health education policies in order to value the oral health as inseparable part of general health, with actions and strategies addressed to the quality of life of this sample of Brazilian elderly.